1970
DOI: 10.1172/jci106334
|View full text |Cite
|
Sign up to set email alerts
|

Fluid reabsorption in Henle's loop and urinary excretion of sodium and water in normal rats and rats with chronic hypertension

Abstract: A B S T R A C T The function of the short loops of Henle was investigated by micropuncture technique in normal rats, in rats with spontaneous hypertension, and in the untouched kidney of rats with experimental renal hypertension. All animals received a standard infusion of 1.2 ml of isotonic saline per hr.With increasing arterial blood pressure (range from 90 to 220 mm Hg), a continuous decrease in transit time of Lissamine green through Henle's loop from 32 to 10 sec was observed. Fractional water reabsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
1

Year Published

1972
1972
1992
1992

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 37 publications
3
24
1
Order By: Relevance
“…Micropuncture data confirm that reabsorption of sodium and water in the loop of Henle was not maximally depressed until arterial blood pressure had been elevated. These findings are in agreement with recent observations in the rat by Bank, Aynedjian, Bansal, and Goldman (35) and Stumpe, Lowitz, and Ochwadt (36) and in saline-loaded hypertensive patients by Buckalew, Puschett, Kintzel, and Goldberg (37). These investigators have demonstrated that sodium transport by the ascending limb of the loop of Henle may be depressed by either acute or chronic elevations of arterial blood pressure.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Micropuncture data confirm that reabsorption of sodium and water in the loop of Henle was not maximally depressed until arterial blood pressure had been elevated. These findings are in agreement with recent observations in the rat by Bank, Aynedjian, Bansal, and Goldman (35) and Stumpe, Lowitz, and Ochwadt (36) and in saline-loaded hypertensive patients by Buckalew, Puschett, Kintzel, and Goldberg (37). These investigators have demonstrated that sodium transport by the ascending limb of the loop of Henle may be depressed by either acute or chronic elevations of arterial blood pressure.…”
Section: Methodssupporting
confidence: 92%
“…Other workers have suggested the importance of either intrarenal humoral factors (35,36) or that the transmission of increased perfusion pressure to vasa rectae will interfere with the peritubular removal of reabsorbate in a manner similar to that thought to be operative for the proximal tubule (38).…”
Section: Methodsmentioning
confidence: 99%
“…Most studies of regulation of sodium excretion in hypertension have been designed to explore the effect of volume-loading. *" 10 ' *° However, the natriuresis resulting from volume expansion is not the same as that resulting from increases in arterial pressure; in fact, these two stimuli increase sodium excretion by different mechanisms. 11 Hence, modulation of pressure natriuresis in hypertension can only be established by examining the effect on sodium excretion of alterations in arterial pressure per se.…”
mentioning
confidence: 99%
“…There was an increase in urinary sodium from 95±16 to 116±17 ueq/min (P < 0.01) but no rise in osmolar clearance, 1.46±0.2 before and 1.39±0.2 ml/min after renal artery stenosis. There was no change in renal blood flow; however, a small, but insignificant, decrease in glomerular filtration from 24.9±1.7 to 22.3±1.9 ml/min occurred after induction of renal hypertension. The fall in GFR accounted for the unchanged osmolar clearance in spite of the significant natriuresis.…”
Section: Resultsmentioning
confidence: 75%
“…Hypertension is known to be associated with an exaggerated natriuresis during volume expansion (23,24), and in rats with Goldblatt or spontaneous hypertension transit time, and fractional water absorption through the loop of Henle is decreased (24). With volume expansion hypertensive animals had a greater increase in urine volume, sodium excretion, osmolar clearance, and TCHZO which was felt to be caused by increased pressure in the medullary circulation decreasing sodium reabsorption in the loop of Henle.…”
Section: Resultsmentioning
confidence: 99%